TRANSLATION ACCURACY OF NOUN PHRASE TRANSLATION IN THE MOVIE ENTITLED â€œRAYA AND THE LAST DRAGONâ€ - Septian Rohmawati Putri; Christina Maya Iriana Sari (Humaniora Scientia, 2022)
A noun phrase is a phrase that may occur within one single word or phrase with a noun as a head. A noun phrase can act as the subject, object, or complement of a clause or as a prepositional complement. This research focused on finding out the translation shift of levelÂ shift in noun phrase translation that occurs in â€œRaya and the Last Dragon,â€ to reveal thetranslation techniques applied in the translation of noun phrases and to assess the translation accuracy of noun phrase translation from the SL to the TL. The theories used in this researchÂ were Catfordâ€™s theory of translation shift, Molina and Albirâ€™s theory of translation technique, and Nababanâ€™s theory of translation accuracy. This research was descriptive qualitativeÂ research. This research showed that 115 noun phrases were found in the data and their translation into Indonesian. The analysis showed that there were six kinds of translation shift of level shift in translating the data. There were 14 translation techniques. In terms of accuracy, 104 data (90.4%) were accurate, 6 data (5.3%) were less accurate, and 5 data (4.3%) were inaccurate.Keywords: noun phrase, translation shift of level shift, translation technique, translation accuracy